KREATIVITAS ABDUL GAFAR DALAM MENCIPTAKAN LAGU POP DAERAH SUMBAWA NUSA TENGGARA BARAT - Risky Asriana Jaelani; Rivaldi Ihsan (Universitas Teknologi Sumbawa, 2023)
This article discusses the creativity of Abdul Gafar, known as Apang, a person who created regional pop songs from Sumbawa, West Nusa Tenggara. Apang, a musician from Sumbawa Besar, is not only a songwriter but also a solo organ player who still exists in the Sumbawa area and its surroundings. His works have succeeded in penetrating the market and competing with other songs in Sumbawa Regency, as well as making a positive contribution to the local music industry. This research applies Rhodes' four